أهمية التربية الاجتماعية وعلاقتها بمقاصد القرآن الكريم والسنة النبوية: قصص أولي العزم من الرسل نموذجًا - ANANDA, FADHLI; Saadeldin Mansour Gasmelsid (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
Social education in Islam has a clear purpose because it comes through stages that begin with individual, family and community guidance and is based on the principles of the Qur’an and Sunnah, the story of the Apostle Ūlū al Āzm is among the stories of the Prophet which has many lessons and benefits that can be taken for life in the world. So this research seeks to uncover the purpose of the story of Rasul Ūlū al Āzm and reveal the meanings of social education contained therein based on verses of the Qur’an and Hadith. This research uses a descriptive method of analysis to look at the concept of social education in Islam based on the principles of the Qur’an and Sunnah. Among the conclusions of this study is that the objectives of the Quran and Sunnah are directly proportional to the concept of education in Islam in producing pious servants on earth, by paying attention to the aspects of the 3 main principles, namely creed, tazkiyah and prosperity, while the story of the Apostle Ūlū alĀzm contained in the Quran and Hadith is a means to achieve these main objectives. Keywords: Ūlū al Āzm, Social Education, A Study of the Maqasid of al-Quran and al-Sunnah.